Time-course transcriptomics reveals the impact of Treponema pallidum on microvascular endothelial cell function and phenotype - Waugh, Sean; Goodyear, Mara C.; Gomez, Alloysius; Ranasinghe, Akash; Lithgow, Karen V.; Falsafi, Reza; Hancock, Robert E. W.; Lee, Amy H.; Cameron, Caroline E. (Frontiers in Microbiology, 2025)
Syphilis, caused by Treponema pallidum subsp. pallidum, is an urgent global public health threat. Syphilis vaccine development has been impeded by limited understanding of the molecular mechanisms that enable T. pallidum to establish and maintain infection. The vascular endothelium is critical for T. pallidum attachment, dissemination, and host immune response initiation; however, the molecular details of T. pallidum-endothelial interactions are incompletely understood. To enhance understanding, we performed time-course transcriptomic profiling on T. pallidum-exposed brain microvascular endothelial cells. These analyses showed T. pallidum exposure altered pathways related to extracellular matrix, growth factors, integrins, and Rho GTPases. The induced transcriptional response was consistent with endothelial to mesenchymal transition, a process involved in fetal development and vascular dysfunction. In cells exposed to T. pallidum, the primary transcription factor associated with this process (Snail) was increased at both the transcript and protein levels, and microscopy analyses demonstrate F-actin cellular contraction. This study provides a comprehensive understanding of the molecular responses of endothelial cells to T. pallidum and identified the host pathways that might cause syphilis disease symptoms, information that could aid in syphilis vaccine design.